The use of google earth as the learning media in geosciences education - Nur Islami (Universitas Riau, 2018)
In studying geosciences, students sometimes face some problems because occasionally they are not able to visualize the earth in their minds. This difficulty is increasingly moreover, if it concerns the distance and height of the topography of the earth, as well as the earth and its relationship to all aspects of life. In this study, the use of google earth as the learning media has been examined to help students understanding in learning geosciences. Students were given guidelines of google earth usage and then students were asked to create a mini project in terms of using of google earth. After that students were given a questioner that is questioned about understanding of the learned material with the help of google earth. The results show that almost all students are fully aware of what they are doing. They also gave an average score of 3.8 (scale 4) in terms of the google earth utilities in learning geosciences. It can be concluded that google earth is able to provide a deeper understanding to the students in studying the concept of physics of earth.